Private View - A2 (InTensions, 2008)
Private View, an installation performance by A2 Company / London, was performed in 2004 by 17 people, (including a 90yr old woman & 3yr old child) at the Institute of Contemporary Arts, London. The installation-performance attempted to explore cause and effect: how the least insignificant action can have an effect on the human body’s sensory system and in our lives, & how the consequences of our actions are rarely considered. Staged in inter-joining gallery rooms, Private View created a space of enactment, of memory, of witnessing, of interconnectedness for performer & audience alike. In one room under the title you’ve cheated again, in front of a microphone, a man on a chair randomly ‘pops’ bubble wrap in his hands. The audio is amplified resulting in the sound of gunfire. His actions are filmed. People lie on the floor & jolt impulsively to the ‘popping’ sound. Audience members are encouraged to lie down & follow. Under the title when I die I would like to take the telephone with me just in case there is one more thing I would like to say, a woman lies under a mound of earth with only one arm revealed holding a mobile phone, which rings intermittently. In another room under the title and I remember that I hadn’t stopped moving on, I had actually been moving non-stop and quite fast, without really paying attention to the fact that soon I was going to be very old, an old lady sits in an armchair, her look fixed on a television screen, broadcasting bubble wrap ‘popped’ between finger & thumb. Desensitized through repeated exposure she falls asleep. A bowl of nuts sit untouched by her side. A2, Anton Mirto & Alit Kreiz, create experimental performance projects exploring new personal, social & emotional language forms. A defining feature of their practice is to represent & engage people from different ages, cultures & backgrounds. Future show: the future of death at WUK in Vienna- April 08 For further information or to contact the company visit www.A2company.org